Factors Associated with Work Fatigue (Occupational Health Study) among Firefighters in City X - Rizqy Kartika Sari; Mirelle Brigitha Violent Tambuwun (Lembaga Pengembangan Kinerja Dosen, 2025)
Firefighters are required to possess excellent physical capacity given that their tasks have major implications for public safety. The volume and criticality of duties often lead firefighters to work more than 12 hours per day for 14 consecutive days. Unmanaged work fatigue can reduce performance and increase occupational safety and health risks. Factors that influence work fatigue include age and Working Period. The aging process, marked by an increase in age, leads to a decrease in work ability due to changes in the functions of body organs, the cardiovascular system, and the body’s hormonal system. Length of service refers to the period of time a person has been employed at a particular office, organization, or institution. A preliminary survey found that 47% of firefighters at the City X Fire and Rescue Agency (DAMKAR) felt moderately fatigued and 13% felt highly fatigued, based on the KAUPK2 instrument. This study aimed to determine factors associated with work fatigue among firefighters in City X. Methods: A cross-sectional design was employed, with data collected at a single point in time, in Mei 2025. The study subjects were firefighters employed by the City X Fire Department. Purposive sampling yielded 56 respondents. Worker Age, working period, and work fatigue were measured using questionnaires. Bivariate relationships among variables were analyzed using the chi-square test. Results: The number of respondents categorized as “not fatigued” was 2, “moderately fatigued” was 21, and “highly fatigued” was 5. Bivariate chi-square analyses indicated significant associations between age and work fatigue, and between tenure and work fatigue (p<0.05). Age was significantly associated with fatigue (p=0.002). Working Period was significantly associated with fatigue (p=0.049). Conclusions: Age and tenure were associated with work fatigue (p<0.05). Future studies were suggested to examine additional factors beyond age and Working Period.